تحديد أهم العوامل المسيطرة على انتشار عنصري النيكل والكادميوم في الرسوبيات الحديثة لشاطئ رأس البسيط (Latakia University Journal -Basic Sciences Series, 2017)
يركز هذا البحث على تحديد نزر بعض العناصر المعدنية الثقيلة (النيكلNi والكادميومCd) في الرسوبيات الشاطئية البحرية لرأس البسيط (اللاذقية) خلال الفترة الممتدة بين خريف 2013و صيف 2014 باستخدام جهاز الامتصاص الذري (Atomic Absorption Spectrophotometer: AAS) بين منطقتين جغرافيتين مختلفتين أحدهما مغلقة والأخرى مفتوحة.تشير نتائج البحث إلى وجود ارتباط هام بين تغير تراكيز العناصر المعدنية المدروسة (Ni&Cd) ونوعية الرسوبيات ومواقع جمع العينات من جهة، وباختلاف مصادر التلوث من جهة أخرى. لوحظ سيادة للرسوبيات الرملية الناعمة مع كميات من الغضار في رسوبيات المنطقة المغلقة مع ارتفاع تراكيز كل من النيكل(755.50mg/Kg) والكادميوم (71.30µg/Kg)، مقارنة مع المنطقة المفتوحة التي كانت أغلبية رسوبياتها رملية متوسطة مع انخفاض تراكيز النيكل(38.85mg/Kg) والكادميوم (13.31µg/Kg).This research focuses on determination the concentration of some heavy metal elements (Nickel Ni and Cadmium Cd) in the coastal water sediments of Ras Al-Basit (Latakia ) during the period that range between Autumn 2013 and Summer 2014 using the Atomic Absorption (Atomic Absorption Spectrophotometer: AAS) at two different (closed and open) geographical regions.The results of the research indicate a correlation monumental between the change in the concentration of studied metallic elements (Ni & Cd), the quality and sediment sampling sites on the one hand, and the sources of pollution on the other. It observed the rule of fine sand with minor amount of clay in the sediments collected from closed area; with high concentrations of both Nickel (755.50mg/Kg), and Cadmium (71.30µg/ Kg), compared with the open area while the majority of the sediments are medium sand with low Nickel and Cadmium concentrations (38.85mg/Kg; 13.31µg/ Kg).